Biomechanical effects of valgus knee bracing: a systematic review and meta-analysis. Issue 2 (February 2015) - Moyer, R.F.; Birmingham, T.B.; Bryant, D.M.; Giffin, J.R.; Marriott, K.A.; Leitch, K.M.
Summary: To review and synthesize the biomechanical effects of valgus knee bracing for patients with medial knee osteoarthritis (OA). Electronic databases were searched from their inception to May 2014. Two reviewers independently determined study eligibility, rated study quality and extracted data. Where possible, data were combined into meta-analyses and pooled estimates with 95% confidence intervals (CI) for standardized mean differences (SMD) were calculated. Thirty studies were included with 478 subjects tested while using a valgus knee brace. Various biomechanical methods suggested valgus braces can decrease direct measures of medial knee compressive force, indirect measures representing the mediolateral distribution of load across the knee, quadriceps/hamstring and quadriceps/gastrocnemius co-contraction ratios, and increase medial joint space during gait. Meta-analysis from 17 studies suggested a statistically significant decrease in the external knee adduction moment (KAM) during walking, with a moderate-to-high effect size (SMD = 0.61; 95% CI: 0.39, 0.83; P < 0.001). Meta-regression identified a near-significant association for the KAM effect size and duration of brace use only ( β, −0.01; 95% CI: −0.03, 0.0001; P = 0.06); with longer durations of brace use associated with smaller treatment effects. Minor complications were commonly reported during brace use and included slipping, discomfort and poor fit, blisters and skin irritation. Systematic review and meta-analysis suggests valgus knee braces can alter knee joint loads through a combination of mechanisms, with moderate-to-high effect sizes in biomechanical outcomes.